Amazonas e Pará: promotorias de justiça ambiental x gestão institucional nos Ministérios públicos - MENDES, Rosivane de Souza (Universidade Federal do Pará, 2019)
This dissertation discusses the legal defense of the environment as a fundamental right, presenting the environmental justice system and legal institutions used in this system. Brings the history of the Public Ministry (MP), identifying its institutional mission, especially in the environmental harvest. It is observed that the Prosecutor of Justice of the capital of Amazonas and Pará there are weaknesses created in the sphere of management, which affect the performance of prosecutors, especially in the environmental area. The survey results indicate that the MPs performance has resulted in the timely execution of the special environmental legislation, due to the set of administrative rules that define an institutional design that vulnerabiliza the performance of the Prosecutor. This scenario makes it difficult to implement the rules of the game, provided for in environmental regulation, growing the legalization of phenomenon of the environment in the Amazon